(untitled) (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to understand and reveal the presentation of the Tor-Tor Raja-Raja Dance at wedding ceremonies in Jorong Silayang, Ranah Batahan Subdistrict, West Pasaman Regency. This research is qualitative research with a descriptive analytical method. The research instrument is the researcher themselves, conducting direct observations in the field and assisted with writing tools, a camera, and a recording device. The types of data used in this study are primary and secondary data. The data collection techniques used in this research are through literature review, observation, interviews, and documentation. The data analysis conducted in this study includes data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the presentation of the Tor-Tor Raja-Raja Dance at weddings in Jorong Silayang has a systematic structure. In its performance, the Tor-Tor Raja-Raja dance generally consists of three main parts: the opening, the main section, and the closing. The presentation of this dance includes several elements, namely dance movements, floor patterns, musical accompaniment, costumes, dancers, props, the performance venue, and implementation procedures that follow customary rules. The dance movements displayed tend to be simple but full of meaning, such as gestures of respect and togetherness. The Tor-Tor Raja-Raja dance is performed by five traditional leaders; it is sacred and can only be performed by descendants of the Nasution royal lineage, and anyone not from the Nasution lineage cannot perform the Tor-Tor Raja-Raja dance. Therefore, the performance of Tor-Tor Raja-Raja is inseparable from binding customary rules and reflects the values of honour and status within the Jorong Silayang community, Ranah Batahan District, West Pasaman Regency.